Implementasi Kurikulum Berbasis Keterampilan dalam Program Pendidikan Kebidanan - Yunas, Aisya Astri (Jayapangus Press, 2025)
The advancement of science and technology, along with the increasing complexity of maternal health service demands, midwifery education curricula must continuously evolve to produce competent and work-ready graduates. One increasingly relevant approach is the implementation of a skills-based curriculum. This study aims to review the implementation of a skills-based curriculum in midwifery education through a systematic literature review. The method used was a systematic literature review by analyzing seven relevant research articles obtained from three major electronic databases: PubMed, ScienceDirect, and Google Scholar, published within the last ten years. The results show that implementing a skills-based curriculum has a significant positive impact, including improved knowledge, clinical skills, and self-confidence among midwifery students. This approach also fosters the development of critical thinking, effective communication, and interprofessional collaboration. Despite challenges in implementation, such as the need for faculty training, adequate facilities, and adjustments in teaching methods, the benefits outweigh the drawbacks. In conclusion, the skills-based curriculum holds great potential in enhancing the quality of midwifery education and ultimately contributes to improving maternal and neonatal healthcare services.